Validation of the Korean version of the avoidance endurance behavior questionnaire in patients with chronic pain - Jeongwi An; Young Hoon Kim; Sungkun Cho (Health and Quality of Life Outcomes, 2018)
Abstract Background The avoidance-endurance model suggests both fear-avoidance responses and endurance-related responses could affect the chronicity of pain. Proper pain intervention requires measuring fear-avoidance responses and endurance-related responses but no Korean language questionnaire has yet been made to measure them. The purpose of this study was to evaluate the validity and reliability of the Korean version of the Avoidance-Endurance Behavior Questionnaire (K-AEQ-Behavior) by adapting the behavioral responses of Avoidance-Endurance Questionnaire into Korean language. Methods The K-AEQ-Behavior was forward and backward translated based on the standards for instrument translation. A total of 136 outpatients with chronic pain of a duration exceeding 3 months were recruited from a pain center at a university hospital in Seoul, Korea. Two weeks later, the K-AEQ-Behavior was re-administered to 36 patients for test-retest reliability. Exploratory factor analysis was performed using principle axis factoring. The internal consistency, test-retest reliability, and concurrent validity of the K-AEQ-Behavior were measured by Cronbach’s ⍺, intraclass correlation coefficient, and Pearson correlation coefficient, respectively. Results Although the four-factor structure (23 items) was derived in the original study, the two-factor structure of avoidance behavior and endurance behavior (21 items) was derived in the exploratory factor analysis of the Korean version in this study. Other results indicated that K-AEQ-Behavior has good internal consistency, test-retest reliability and concurrent validity. Conclusion This study suggests that the K-AEQ-Behavior is a reliable and valid instrument for assessing avoidance behavior and endurance behavior in patients with chronic pain.